2018
DOI: 10.1016/j.cub.2017.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Collective Aggressiveness Favors Social Susceptibility in Social Spiders

Abstract: SUMMARY Particularly socially influential individuals are present in many groups [1–8], but it is unclear whether their emergence is determined by their social influence versus the social susceptibility of others [9]. The social spider Stegodyphus dumicola shows regional variation in apparent leader-follower dynamics. We use this variation to evaluate the relative contributions of leader social influence versus follower social susceptibility in driving this social order. Using chimeric colonies that combine po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…We measured colonies’ aggressiveness by placing dummy prey (1 cm sections of dead leaf) 4 cm from the rim of the nest basket, and vibrating it with a handheld vibratory device until spiders emerged and seized the dummy prey (Pruitt et al., ), between 1000 and 1600 hr. We recorded the latency of the first spider to contact the dummy and the number of spiders moving towards the dummy at this time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We measured colonies’ aggressiveness by placing dummy prey (1 cm sections of dead leaf) 4 cm from the rim of the nest basket, and vibrating it with a handheld vibratory device until spiders emerged and seized the dummy prey (Pruitt et al., ), between 1000 and 1600 hr. We recorded the latency of the first spider to contact the dummy and the number of spiders moving towards the dummy at this time.…”
Section: Methodsmentioning
confidence: 99%
“…Social organisms provide an interesting case study for evolutionary ecologists, because trait differences occur at both the individual‐level and between groups, in terms of their collective traits (Bengston & Jandt, ; Jandt et al., ; Wray & Seeley, ). Like individual traits, a growing body of evidence conveys that group traits are often associated with group success (Gordon, ; Shaffer et al., ; Wray, Mattila, & Seeley, ), and that these links can vary between environments (Pruitt & Goodnight, ; Pruitt et al., ). Site‐specific selection may therefore contribute to biodiversity by promoting intraspecific variation and local adaptation in group‐level traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The social spider Stegodyphus dumicola is native to central and southern Africa (Johannesen et al 2007) and has been widely used to study the evolutionary ecology of group living (Pruitt et al 2019(Pruitt et al , 2018Berger-Tal et al 2014;Grinsted et al 2013). We collected three colonies of aproximitly 80 individuals each from Kalkrand, Namibia, in February 2017 and housed them in the lab, feeding them with crickets ad libitum until RNA extraction.…”
Section: Expression Profiles Of Rapidly Evolving Genes In Four Tissuementioning
confidence: 99%
“…Several recent studies on 'collective personality' or 'colonylevel personality' have linked variation in group behavior with group growth rates (Pruitt 2012), productivity (Modlmeier et al 2012), and resource allocation strategies (Bengston et al 2017). Some studies have revealed that the relationship between group behavior and success can differ situationally (Pruitt et al 2018a). However, the broader ecological consequences of such between-group variation have not been rigorously evaluated, despite the fact that animal social groups often have large impacts on their environments (Human and Gordon 1996, Goheen and Palmer 2010, Sih et al 2011).…”
Section: Introductionmentioning
confidence: 99%